Economics and Performance Efficiency of Onion Farmers in Aliero Local Government Area of Kebbi State, Nigeria - K, Yayaya; Umar, S (Annals of Arid Zone, 2019)
The study investigated profitability and technical efficiency of irrigated onion production in Aliero Local Government Area of Kebbi State, Nigeria. The primary data used for the study were developed using structured questionnaire administered to 120 randomly selected onion farmers in 2017 production season. Descriptive statistics, farm budgeting (gross margin, net farm income, gross ratio, operation ratio, return on investment) and Cobb-Douglas stochastic frontier production function model were employed in analyzing the data. The estimated gross margin, net farm income, gross ratio, Operating ratio, and Return on capital investment were N 446,219.28, N 427,578.82 per hectare, 0.25, 0.22 and 3.61 respectively. The mean efficiency was 83.6% indicating that there was a 16.4% opportunity for improving the efficiency. The farmers’ educational level, years of farming experience and access to extension service significantly influenced the farmers’ efficiency positively. It is recommended that relevant policies that would enhance the technical skill of the farmers and access to extension services should be developed by the stakeholders. Key words: Cobb-douglas, gross margin, onion farms, profit, stochastic frontier production function.